Purification and characterization of a hyperthermostable Mn-superoxide dismutase from Thermus thermophilus HB27. - Liu, J; Yin, M; Zhu, H; Lu, J; Cui, Z (2011)
Thermostable Mn-dependent catalases are promising enzymes in biotechnological applications. In the present study, a Mn-containing superoxide dismutase of the hyperthermophilic Thermus thermophilus HB27 had been purified and characterized by a two-stage ultrafiltration process after being expressed in E. coli. The enzyme was highly stable at 90°C and retained 57% activity after heat treatment at 100°C for 1 h. The native form of the enzyme was determined as a homotetramer by analytical size exclusion chromatography and sodium dodecyl sulfate-polyacrylamide gel electrophoresis. The final purified enzyme had an isoelectric point of 6.2 and a high α-helical content of 70%, consistent with the theoretical values. This showed that the purified SOD folded with a reasonable secondary structure.